Feasibility of compost latrines and private sector participation in building and operating compost latrines in urban primary schools - Chunga, Richard David (Cranfield University, 2009)
This research was conducted in Blantyre Urban in Malawi to identify potential markets for human compost and to assess the feasibility of ecological sanitation and private sector participation in building and operating compost latrines in primary schools. In this research, urban farmers, landscape managers and nursery owners were asked to indicate their willingness to pay for human compost. The research revealed that over 70% of urban farmers and tree/flower nursery owners are willing to use human compost and to pay MK350 to MK500 per 50kg bag of human compost. Although there are potential buyers of human compost in Blantyre Urban, the study has shown that it is highly unlikely that entrepreneurs would be motivated to build and operate compost latrines in primary schools because of high investment cost and low returns. The maintenance of latrines in primary schools is under the responsibility of school management committees. However, due to lack of funding, the school management committees are unable to maintain damaged latrines or to build extra latrines. Due to lack of funding for maintenance, 512 flush toilets have been abandoned and 27 pit latrines can’t be fully utilised. The failure of school management committees to maintain damaged latrines or to build extra latrines has resulted into a widespread shortage of latrines in primary schools such that over 120 pupils use a single toilet. Building and operating compost latrines was found to be more profitable to schools than to entrepreneurs because schools receive support for building and operating school latrines. Ecological sanitation could offer urban primary schools an opportunity to improve school sanitation and to generate income by selling human compost.
Keywords: human compost; urban farmers; Blantyre Urban; urban farmers; primary schools; flush toilets